Answer

Verified

341.1k+ views

**Hint:**Here, we will simply add and subtract square of a constant and write the term containing $n$ such that it forms a term in a form $2ab$, thus, this will help us to apply the square identities and thus, ‘complete the square’ and solve it further to find the required roots of the given quadratic equation.

**Formula Used:**

${\left( {a - b} \right)^2} = {a^2} - 2ab + {b^2}$

**Complete step-by-step answer:**

The given quadratic equation is:

$2{n^2} - 7n + 3 = 0$

Now, dividing both sides by 2, we get,

${n^2} - \dfrac{7}{2}n + \dfrac{3}{2} = 0$

Now, since, we are required to solve this question using completing the square, hence, we will write this quadratic equation as:

${\left( n \right)^2} - 2\left( n \right)\left( {\dfrac{7}{4}} \right) + {\left( {\dfrac{7}{4}} \right)^2} - {\left( {\dfrac{7}{4}} \right)^2} + \dfrac{3}{2} = 0$

Hence, even if this quadratic equation was not a perfect square, but we tried to make it a perfect square by adding and subtracting the square of a constant such that, we complete the square by making the identity, ${\left( {a - b} \right)^2} = {a^2} - 2ab + {b^2}$

Hence, using this identity, we get,

${\left( {n - \dfrac{7}{4}} \right)^2} - \dfrac{{49}}{{16}} + \dfrac{3}{2} = 0$

$ \Rightarrow {\left( {n - \dfrac{7}{4}} \right)^2} + \dfrac{{ - 49 + 24}}{{16}} = 0$

Hence, we get,

$ \Rightarrow {\left( {n - \dfrac{7}{4}} \right)^2} - \dfrac{{25}}{{16}} = 0$

Adding $\dfrac{{25}}{{16}}$ on both sides,

$ \Rightarrow {\left( {n - \dfrac{7}{4}} \right)^2} = \dfrac{{25}}{{16}}$

$ \Rightarrow {\left( {n - \dfrac{7}{4}} \right)^2} = {\left( {\dfrac{5}{4}} \right)^2}$

Taking square root on both sides, we get

$ \Rightarrow \left( {n - \dfrac{7}{4}} \right) = \pm \dfrac{5}{4}$

Adding $\dfrac{7}{4}$ on both the sides, we get,

$ \Rightarrow n = \pm \dfrac{5}{4} + \dfrac{7}{4}$

Hence,

$n = \dfrac{5}{4} + \dfrac{7}{4} = \dfrac{{5 + 7}}{4} = \dfrac{{12}}{4} = 3$

Or $n = - \dfrac{5}{4} + \dfrac{7}{4} = \dfrac{{7 - 5}}{4} = \dfrac{2}{4} = \dfrac{1}{2}$

Therefore, the roots of the given quadratic equation $2{n^2} - 7n + 3 = 0$ are 3 and $\dfrac{1}{2}$

Thus, this is the required answer.

**Note:**

If in the question, it was not mentioned that we have to use the method of completing the square, then, we could have used the quadratic formula to solve the given quadratic equation.

Given quadratic equation is $2{n^2} - 7n + 3 = 0$

Now, dividing both sides by 2, we get,

${n^2} - \dfrac{7}{2}n + \dfrac{3}{2} = 0$

Comparing this with the general quadratic equation i.e. $a{x^2} + bx + c = 0$

We have,

$a = 1$, $b = \dfrac{{ - 7}}{2}$ and $c = \dfrac{3}{2}$

Now, we can find the roots of a quadratic equation using the quadratic formula, $n = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$

Hence, for the equation ${n^2} - \dfrac{7}{2}n + \dfrac{3}{2} = 0$, substituting$a = 1$, $b = \dfrac{{ - 7}}{2}$and $c = \dfrac{3}{2}$, we get

$n = \dfrac{{\dfrac{7}{2} \pm \sqrt {{{\left( {\dfrac{{ - 7}}{2}} \right)}^2} - 4\left( 1 \right)\left( {\dfrac{3}{2}} \right)} }}{{2\left( 1 \right)}}$

$ \Rightarrow n = \dfrac{{\dfrac{7}{2} \pm \sqrt {\dfrac{{49}}{4} - 6} }}{2} = \dfrac{{\dfrac{7}{2} \pm \sqrt {\dfrac{{49 - 24}}{4}} }}{2} = \dfrac{{\dfrac{7}{2} \pm \sqrt {\dfrac{{25}}{4}} }}{2}$

Solving further, we get,

\[ \Rightarrow n = \dfrac{{\dfrac{7}{2} \pm \dfrac{5}{2}}}{2} = \dfrac{{7 \pm 5}}{4}\]

Hence, we get,

\[n = \dfrac{{7 + 5}}{4} = \dfrac{{12}}{4} = 3\]

Or \[n = \dfrac{{7 - 5}}{4} = \dfrac{2}{4} = \dfrac{1}{2}\]

Therefore, the roots of the given quadratic equation $2{n^2} - 7n + 3 = 0$ are 3 and $\dfrac{1}{2}$

Thus, this is the required answer.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Why is the adrenaline hormone called fight or flight class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Differentiate between lanthanoids and actinoids class 12 chemistry CBSE

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.

Give 10 examples of unisexual and bisexual flowers

Open circulatory system is present in I Arthropods class 12 biology CBSE

Name the highest peak of the Indian Himalayas class 8 social science CBSE